ANALISIS KOMITMEN PROFESIONAL DAN SOSIALISASI ANTISIPATIF SERTA HUBUNGANNYA DENGAN WHISTLEBLOWING (Studi Persepsi Mahasiswa Akuntansi Universitas Islam Malang) - Isma Lutfiana; Abdul Wahid Mahsuni; Siti Aminah Anwar (Universitas Islam Malang, 2020)
ABSTRACT The purpose of this study was to analyze the effect of professional commitment and anticipatory socialization and its relationship with whistleblowing behavior. The population in this study were 193 students of semester V Malang Islamic University, and used a purposive sampling method using 84 students as respondents.This study uses primary data collected through questionnaires. To test the relationship between professional commitment and anticipatory socialization with whistleblowing behavior, multiple regression tests are used with SPSS ver 16 software.The results showed that professional commitment and anticipatory socialization simultaneously had a significant effect on whistleblowing behavior. The partial test results show that the variable professional commitment has a positive and significant effect on whistleblowing behavior. Meanwhile, the anticipatory socialization variable has a negative and significant effect on whistleblowing behavior. Keywords: commitment professional, anticipatory socialization, whistleblowing.